Modifikasi Lapangan Woodball Portable Sebagai Sarana Latihan Pukulan Gate-In - Syafutra, Wawan; Remora, Hengky (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to develop a portable woodball court as a means of practicing gate-in shots. This development is motivated by weather constraints and the limitations of permanent field facilities which often hinder woodball practice activities. The research method used is Research and Development (R&D) with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The products developed are validated by media, language, and material experts, and tested for practicality through coaches and athletes at the Woodball Academy Silampary. The validation results show that this product is very valid with an average validity of 90.5%. In addition, the practicality test showed that portable woodball courts were very practical to use, with a percentage of 86.4%. In addition, the portable woodball court proved to be effective with a t-value of 2,739 >1,761 (t k-df 14) and a P value (sig.) of 0.016 < 0.05. This modification provides innovative solutions to overcome weather constraints and facility limitations, as well as support the socialization of woodball in various places. Conclusion, this portable woodball court can be an effective alternative in increasing interest and achievement in woodball sports. Keywords: Woodball, Portable, Gate-In Shot, Court Modification